Unveiling pre-service English teachers' perceptions of differentiated instruction - Sukarno, Sukarno; Riyadini, Maria Vineki; Jinabe, Megan; Lestari, Aryanti Eka (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2024)
Implementing differentiated instruction (DI) has become imperative, particularly with its integration into the Kurikulum Merdeka in Indonesia. It is an approach that customizes instruction to cater to students' needs. This study aimed to unveil the general perceptions of pre-service English teachers regarding DI, explore their understanding and practices within the framework of DI, and identify challenges in its implementation. This study applied a quantitative approach with a survey research design with EFL pre-service teachers as the participants. The research employed a structured questionnaire as the primary instrument and substantiated each item through validation procedures, including Cronbach's alpha analysis. The findings showed a comprehensive overview of pre-service English teachers' general perspectives on DI that influence their practical application of related techniques. These insights contributed to a deeper understanding of the efficacy of DI and informed pedagogical practices, teacher preparation programs, and curriculum development. This research divulged the crucial role of pre-service English teachers' perceptions in implementing DI in teaching and learning contexts. Additionally, the study highlighted challenges pre-service teachers face, such as time constraints, limited resources, and large class sizes, emphasizing the need for collaborative efforts among stakeholders to address these challenges. The outcomes of this study were expected to inform related parties about the significance of tailored instruction in fostering effective and inclusive instruction environments to reach educational goals.